Uma análise bioecológica sobre atividade física e comportamento sedentário da escola de educação infantil no município de Tocantínia - TO - Lima, Luan Pereira (Universidade Federal do Tocantins, 2024)
Preschoolers have been in sedentary behavior for a long time in schools, not reaching the minimum physical activity recommended by international parameters, causing damage to integral development, as well as increased sedentary childhood. One of the factors that corroborates this is the environment and the people directly involved with preschoolers. Thus, the general objective of this paper is to analyze family and school-related aspects of the environment regarding the influence on sedentary behavior and physical activity level of preschoolers. A field research was conducted with 26 parents and 5 teachers / monitors of preschoolers living in Tocantínia-TO. Parents answered two questionnaires, one related to the activities that are performed inside and outside the school environment by their children and the other related to their physical activity level, the teachers / monitors answered only one questionnaire, also related to the activities that their your students perform in and out of school. This study has an ecological design and the analysis of the two main microsystems showed that the daily frequency of physical activities performed by preschoolers is low, 13% at home (parents) and 7% at school (teachers), while daily activities facilitating sedentary behavior were 25% at home (parents) and 17% at school (teachers). In addition, the preschoolers' physical activity level was low, 50% of the children during an ordinary day of the week and 35% during a weekend day were categorized as poorly active (less than 1h / day of activity). 38% of children during an average day of the week and 54% during a weekend day were in the category with the highest exposure to screen time (more than 2h / day). Statistical analysis indicated that the younger the parent and the more important the parent's sedentary activities in school, the more likely they are to be exposed to screen time on weekends. The analyzed contexts indicate that parents and teachers tend not to offer physical activities, according to international recommendations, to their children / students, even considering this important practice